NUANSA MAKNA SINONIM ADJEKTIVA SIKAP BATIN DALAM BAHASA INDONESIA - Nila Oktami; Ngusman Abdul Manaf; Novia Juita (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The purpose of this study was to determine the pair of synonyms and nuances of the meaning of the pair of synonyms of the Indonesian mental attitude adjective. This research is qualitative research using the descriptive method. The data of this study are the basic adjectives of the inner attitude of Indonesian. The results of this study indicate that (1) there are 26 pairs of Indonesian mental attitude adjectives that are proven to be synonymous and (2) all pairs of Indonesian mental attitude adjectives that prove synonymous with meaning nuances. Not all Indonesian mental attitude adjectives that have synonym and most synonymous pairs are adjunctive nuances of meaning on cognitive meaning anda a small part of emotive menaing.